PENGARUH KESEHATAN DAN KESELAMATAN KERJA SERTA PELATIHAN KERJA TERHADAP KINERJA KARYAWAN UNIT OPERASIONAL REDRYING & THRESHING KAREB BOJONEGORO - TEGUH PURNAMA, OKTAVIAN (Jurnal Ilmu Manajemen (JIM), 2016)
The high employee performance indicates there possibility an accident level are also high. That is necessary to apply and their affirmation of the implementation of occupational safety and health. This study aimed to analyze the influence of occupational safety and health and training on employee performance. The samples in this study using non-probability sampling technique. The sample consisted of 238 respondents employees of Cooperative KAREB Bojonegoro. The data collection is done by using a questionnaire. After that tested the validity, reliability and data analysis technique processed using SPSS version 18. The results of this study show that health and safety significant positive effect on employee performance, job training significant positive effect on employee performance. Simultaneousl. health , safety and job training significantly influence employees performance amounted to 78,3%, while the remaining 21,7% is explained by other factors. Keywords : Health and Work Safety, Vocational Training, Employee Performance.